Making globalization socially sustainable - Bacchetta, Marc (WTO GenevaCH, 2011)
Focuses on the three main themes that have received significant attention in recent debates on the social aspects of globalisation, viz. employment, uncertainty and inequality. Aims to provide insights - based on state-of-art research - into the mechanism that link globalisation to each of the three labour market aspects and to provide an overview of the available statistical evidence on these three linkages.